2020
DOI: 10.1111/tgis.12654
|View full text |Cite
|
Sign up to set email alerts
|

How urban places are visited by social groups? Evidence from matrix factorization on mobile phone data

Abstract: This research attempts to build a unified framework for distinguishing the spatiotemporal visit patterns of urban places by different social groups using mobile phone data in Harbin, China. Social groups are detected by their social ties in the ego‐to‐ego mobile phone call network and are embedded in physical space according to their home locations. Popular urban places are detected from user‐generated content as the basic spatial analysis unit. Coupling subscribers’ footprints and urban places in physical spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 75 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Another stream of the literature explained the effects of individuals’ psychological factors on their representations of the physical world. The literature found that individuals’ time and distance estimations are biased by cognitive (Kang et al , 2020), social (Zhao et al , 2018) and emotional factors (Han et al , 2018). The literature showed that individuals make different spatial decisions, determined by psychological factors, even when exposed to similar time–space constraints (Grinberger and Shoval, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another stream of the literature explained the effects of individuals’ psychological factors on their representations of the physical world. The literature found that individuals’ time and distance estimations are biased by cognitive (Kang et al , 2020), social (Zhao et al , 2018) and emotional factors (Han et al , 2018). The literature showed that individuals make different spatial decisions, determined by psychological factors, even when exposed to similar time–space constraints (Grinberger and Shoval, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…NMF is a very robust technique to detect hidden patterns in a data matrix whose entries are not negative (Lee & Seung, 1999). In particular, the method has been used to unveil urban spatial clusters based on human mobility behaviors (Kang, Shi, Wang, & Liu, 2020).…”
Section: Spatial Colocationmentioning
confidence: 99%
“…NMF is a very robust technique to detect hidden patterns in a data matrix whose entries are not negative (Lee & Seung, 1999). In particular, the method has been used to unveil urban spatial clusters based on human mobility behaviors (Kang, Shi, Wang, & Liu, 2020). In our case, we derived a social–spatial matrix, which captures the frequency of activities occurring in different spatial units by different social groups.…”
Section: Case Studymentioning
confidence: 99%
“…This mobile data provides an understanding of human mobility [4]. The challenges of smart cities and the need for trade-offs between the use of data and privacy are discussed [2] There are several research papers on the adoption of mobile data to understand urban mobility in urban landscapes [8,14,18]. These digital footprints can be used to understand the number of visitors who have visited art places, as well as their time spent at the different art places.…”
Section: Introductionmentioning
confidence: 99%